Perencanaan Struktur Atas Bangunan Gedung Menggunakan Sistem Rangka Bresing - Putra, M.R.; Amir, F.; Listiawaty, H.; Sutrisno, M. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
After the 2018 earthquake, a number of constructions in Palu City, especially buildings, grew rapidly. In the construction of buildings using steel structures, the use of braces aims to reduce displacement and increase the capacity of shear forces to resist cracking. Steel produces greater ductility when compared to other structural materials, so it is a major requirement in designing earthquake-resistant steel structures. In this study, the structure of the building was designed to be 3 (three) stories in educational purpose. The structural system has a dual system combination Special Moment Resisting Steel Frame System (SMRF) and a lateral force resisting system, namely a Special Concentric Brace Frame System (SCBF). Steel material used are BJ 41 quality (fy = 250 MPa; fu = 410 MPa) and concrete using quality f'c = 25 MPa. The loads acting on the structure are dead load, live load, wind load, rain load, and earthquake load. The results of the structural analysis are: 99,42% mass participation is obtained for the x direction in mode 4 and 98,97% for the y direction in mode 5, the SRSS method was used to combine the number of mode varieties used, the obtained dynamic earthquake shear force response spectrum (x direction = 281993,31 kg and y direction = 280187,36 kg) has exceeded the equivalent static earthquake shear force (x direction and y direction = 280096,09 kg), the displacement that occurs in the x direction and y direction does not exceed the allowable displacement of 34,615 mm, the stability coefficient obtained in the x-direction and y-direction does not exceed the P-Delta effect limit of 0,1 and the structural stability limit of 0,0909, the structure does not occur horizontal irregularities and vertical irregularities, the Special Moment Resisting Steel Frame System (SMRF) has exceeded the percentage of 25% (x direction = 62,49% and y direction = 58,26%), the structural performance level in the x direction and y direction is in Damage Control condition.